Sword in the stars - Capetta, A. R.; McCarthy, Cori (JIMMY Patterson Books, Little, Brown and Company, 2020)
"In this epic sequel to Once & Future, Ari and her Rainbow knights must pull off a Holy Grail heist thousands of years in the past -- without destroying their own destinies. Ari Helix may have won her battle against the tyrannical Mercer corporation, but the larger war has just begun. Ari and her cursed wizard Merlin must travel back in time to the unenlightened Middle Ages and steal the King Arthur's Grail -- the very definition of impossible. It's imperative that the time travelers not skew the timeline and alter the course of history. Coming face to face with the original Arthurian legend could produce a ripple effect that changes everything. Somehow Merlin forgot that the past can be even more dangerous than the future . . ." ~ Amazon.